The 12 biggest breakthroughs in space technology - Morey, Allan (Technology breakthroughs II., 2019)
Examines twelve inventions and breakthroughs in space technology from the inventions of telescopes to reusable rockets and vehicles for deep space travel. Includes a glossary and resources for further information.